Association of endothelial nitric oxide synthase gene (G894T) polymorphism and hypertension in diabetic Bataknese patients - Jelita Siregar; Ratna Akbari Ganie; Dharma Lindarto; Erna Mutiara; Delfitri Munir (Medicinski glasnik, 2020)
Aim: To assess endothelial nitric oxide synthase (eNOS) gene (G894T) polymorphism and nitric oxide (NO) level in hypertensive diabetic Bataknese patients. Methods: A hospital-based, case control study (hypertensive and normotensive diabetic patient) was conducted. Genotyping of eNOS gene (G894T) was done using polymerase chain reactionrestriction fragment length polymorphism (PCR-RFLP). Nitric oxide was quantified by sandwich enzyme-linked immunosorbent assay (Sandwich ELISA). Results: GT polymorphism and T allele were higher in the hypertensive diabetic patients, 37.5% (p=0.6) and 54% (p=0.39), respectively. Nitric oxide level tended to be lower in the hypertensive diabetic patients (88.87µmol/L) comparing to the normotensive (95.42 µmol/L (p=0.54), as well as GT and TT polymorphism type (p=0.75). Conclusion: eNOS gene (G894T) polymorphism is not associated with NO level and hypertension in the diabetic Bataknese patients.
Keywords: diabetes mellitus; hypertension; nitric oxide; nitric oxide synthase type III; polymorphism